Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian Mie Gacoan di Pancing : (Study Kasus pada Mahasiswa Pendidikan Ekonomi Tahun 2021) - Muamar Rinaldi; Endang Endang; Fera Daniaty Nababan; Fransiska Adelia Br Sinulingga; Putri Titin Sianturi; Rafli Ramli; Samuel Tobing (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This research aims to analyze customer satisfaction with purchasing decisions at Mie Gacoan Pancing, especially among Economic Education students class of 2021, Medan State University. Using literature review and interview methods, this research evaluates factors such as product quality, price and service that influence customer satisfaction. The findings show that product quality, especially the taste and texture of the noodles, is the main attraction, while the affordable price supports the preferences of students on a limited budget. However, service quality is still a challenge, such as irregular queues and unfriendly staff attitudes. High customer satisfaction contributes to repeat purchase decisions and word-of-mouth recommendations, while dissatisfaction can reduce customer loyalty. This research underlines the importance of improving service and maintaining consistent product quality to improve customer experience and support business sustainability in the culinary sector.